Evaluasi Penerimaan dan Penggunaan Aplikasi PLN Mobile di Kota Palembang Dengan Metode Technology Acceptance Model (TAM) - Robby Prabowo; Edi Surya Negara; Prihambodo Hendro Saksono (PPPM Institut Teknologi Pagar Alam, 2024)
The Technology Acceptance Model (TAM) is a model used to explain and predict attitudes towards the use of a technology. The TAM method has four main variables: (1) Perceived Usefulness (PU); (2) Perceived Ease of Use (PE); (3) Attitude; and (4) Behavioral Intention of Use (BI). This study examines how PLN Mobile can be accepted and adopted based on the four variables mentioned above. The research was conducted in Palembang City with 90 respondents. Data collection was carried out by distributing questionnaires, and 18 indicators were used, measured on a Likert Scale. The data analysis technique used is Partial Least Squares structural equation modeling. The results of this study indicate that Perceived Ease of Use has a significant positive effect on Perceived Usefulness, Perceived Ease of Use has a significant positive effect on Attitude Towards Using, Perceived Ease of Use has no significant effect on Behavioral Intention of Use, Perceived Usefulness has a significant positive effect on Attitude Towards Using, Perceived Usefulness has a significant positive effect on Behavioral Intention of Use, and Attitude Towards Using has a significant positive effect on Behavioral Intention of Use. The theoretical implications of this study suggest that integrating contextual factors such as UI and UX and the development of an enhanced theoretical model can provide a better understanding of technology adoption and application usage. The practical implications of the findings are that to increase the adoption and use of the PLN Mobile application, it is important to focus on improving usability and ease of use, an attractive and functional UI design, as well as effective communication and support strategies.